Micronutrient status and associated factors of anemia among undernourished children of 5-18 years: First study from Himalayan foothills - KS Aswanth; Nikhil Rajvanshi; Vinod Kumar; Swathi Chacham; Manisha Naithani; Ranjeeta Kumari; Prashant K. Verma (Journal of Family Medicine and Primary Care)
Purpose: Undernutrition in children is a critical worldwide concern that hampers both their physical and cognitive growth. The nutritional status of school-going children and adolescents remains insufficiently addressed with no comprehensive data. This is the first study from the Himalayan foothills that aims to assess the clinical and laboratory aspects of anemia with micronutrient status in undernourished children above the age of five along with association of clinical features with anemia severity. Materials and Methods: A cross-sectional study was conducted involving children aged 5-18 years with undernutrition in a tertiary hospital in North India over eighteen months. We observed the prevalence of anemia, its morphological type, micronutrient status, clinical features, and demographic parameters of these children. The association of various clinical features and anthropometric parameters with the severity of anemia was determined. Results: Of the 200 children who were enrolled in the study, 77% were found anemic, with the proportion of mild, moderate, and severe anemia being 18.2%, 46.8%, and 35%, respectively. Iron (67%) was the most common micronutrient deficient in these children with a significant number suffering from vitamin B12 (53.9%) deficiency. Folic acid deficiency was relatively low (10.4%). Body mass index (P = 0.009), fatigability (P = 0.001), pallor (P ≤ 0.001), poor academic performance (P = 0.023), and knuckle hyperpigmentation (P = 0.018) were significantly associated with the severity of anemia. Conclusion: Despite the significant tread in various aspects of human development, undernutrition and anemia remain a formidable challenge, especially in developing countries. A high proportion of anemia in undernutrition indicates the gravity of the issue, yet not received the deserved attention.